Case Report: A combination of chimeric CYP11B2/CYP11B1 and a novel p.Val68Gly CYP11B1 variant causing 11β-Hydroxylase deficiency in a Chinese patient - Li, Jialin; Zhang, Fenglan; Xu, Miao; Qiu, Hao; Zhou, Cheng; Li, Li; Qin, Lan (Frontiers in Endocrinology, 2023)
Introduction: 11β-Hydroxylase deficiency (11β-OHD, OMIM#202010) is the second most common form of congenital adrenal hyperplasia (CAH) caused by pathogenic variants in the CYP11B1 gene. Both single nucleotide variations (SNV)/small insertion and deletion and genomic rearrangements of CYP11B1 are important causes of 11β-OHD. Among these variant types, pathogenic CYP11B2/CYP11B1 chimeras only contribute to a minority of cases. Heterozygote cases (chimera combined with SNV) are very rare, and genetic analysis of these cases can be challenging. Case presentation: We presented a suspected 11β-OHD female patient with incomplete virilization, adrenal hyperplasia, and hypokalemia hypertension. Whole exome sequencing (WES) revealed that the patient carried both a chimeric CYP11B2/CYP11B1 and a novel missense variant, NM_000497.4: c.203T>G, p.Val68Gly (chr8:143961027) in CYP11B1, which were confirmed by CNVplex and Sanger sequencing, respectively. The patient's manifestations and genetic findings confirmed the diagnosis of 11β-OHD, and oral dexamethasone was administered as a subsequent treatment. Conclusion: This report showed a rare CYP11B2/CYP11B1 chimera combined with a novel missense variant in a 11β-OHD female patient. The result expands variant spectrum of CYP11B1 and suggests that both chimera and CYP11B1 variant screening should be performed simultaneously in suspected cases of 11β-OHD. To our knowledge, this is the first report about CYP11B2/CYP11B1 chimera detected by WES analysis. WES combined with CNV analysis is an efficient method in the genetic diagnosis of this rare and complex disorder.